Lagring av skogsflis med och utan täckning : substansförlusters påverkan av nederbörd och vind - Wetterholm, Daniel (SLU/Dept. of Energy and Technology, 2021)
In the supply chain for wood chips, storage is a neccesary part due to seasonal demand. During storage there are several mechanisms occuring, cell respiration, biological degradation and thermo-chemical oxidative reaction. All of the mentioned mechanisms lead to increased temperature, loss of dry matter and energy. They all thrive under certain conditions where moisture, temperature and oxygen is important factors. SLU(The Swedish University of Agricultural Sciences) made studies on several piles of wood chips to explore the effect of covering the piles with a water-resistant and vapourpermeable fabric (Anerud, et al., 2018). Rewetting can lead to dry matter losses and energy losses, with this method rewetting can be prevented. This would mean a lower cost when storing wood chips. This study analyses data from two piles, in Vagersta and Nykvarn, both of the piles were partly covered by this water resistant and semi-permeable fabric. Regression analysis is used to explore the correlation between precipitation and temperature in the piles. Results from collected samples is analysed to compare fuel quality between the covered and uncovered parts and also between periods with higher and lower temperatures. All of this is analysed in upper and lower points of the pile to conclude differences. Results showed that i Nykvarn where the pile was dry and fresh the uncovered upper part experienced huge temperature spikes after the first rain fall. A daily mean of 145 ºC at most and in that part of the pile the dry matter losses was 5,3% after about three weeks of storage. The sample from the lower part showed 2% dry matter losses after three weeks and in the covered part the losses were 1%. After this initial period, rewetting started to affect the lower part of the pile more and higher temperatures were seen there. In Vagersta the initial moisture content was higher and the material was less fresh. This meant that precipitation did not trigger biological processes to any bigger extent. The first months both temperatures and dry matter losses were similar between upper, lower and covered points. No connection between precipitation and temperature was seen. The effect of rewetting started to show after that point, temperatures and dry matter losses were higher in the uncovered part. Conclusions made was that using a semi-permeable fabric can help retain more fuel and therefore lower the cost when storing wood chips. If the pile is dry and fresh, covering can be crucial even for short term storage. The highest temperatures were measured after precipitation on a dry and fresh pile.